Pengaruh Celebrity Endorsement, Brand Image Dan Testimoni Terhadap Keputusan Pembelian Konsumen Produk Sepatu Aerostreet (Studi Kasus Pada Mahasiswa Unisma) - Nashiq, Andika Fatkhin; Widarko, Agus; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The objective of this research is to explore the effects of Celebrity Endorsement, brand image, alongside consumer testimonials regarding the purchase decisions of Aerostreet shoes among students of Universitas Islam Malang. The research employed a quantitative approach using questionnaires Utilizing a By applying a Likert scale alongside multiple linear regression, the findings demonstrate that all three variables significantly affect purchase decisions both simultaneously and partially, with Celebrity Endorsement emerging as the dominant factor. These findings highlight the importance of marketing strategies based on public figures, strong brand image, and social validation in enhancing consumer trust and attractiveness toward local brands. Keywords: Celebrity Endorsement; Brand Image; Testimonials; Purchase Decision;   Aerostreet